Nuclear autophagy degrades a geminivirus nuclear protein to restrict viral infection in solanaceous plants - Li, Fangfang; Zhang, Mingzhen; Zhang, Changwei; Zhou, Xueping (The New phytologist, 2020)
• Autophagy is an evolutionarily conserved degradation pathway in the cytoplasm and has emerged as a key defense mechanism against invading pathogens. However, there is no evidence showing nuclear autophagy in plants. • Here, we show that a geminivirus nuclear protein, C1 of tomato leaf curl Yunnan virus (TLCYnV) induces autophagy and interacts directly with the core autophagy-related protein ATG8h. The interaction between ATG8h and C1 leads to the translocation of the C1 protein from the nucleus to the cytoplasm and the decreased protein accumulation of C1, which is dependent on the exportin1-mediated nuclear export pathway. The degradation of C1 is blocked by autophagy inhibitors and compromised when the autophagy-related genes (ATGs) ATG8h, ATG5, or ATG7 are knocked down. Similarly, silencing of these ATGs also promotes TLCYnV infection in Nicotiana benthamiana and Solanum lycopersicum plants. • The mutation of a potential ATG8 interacting motif (AIM) in C1 abolishes its interaction with ATG8h in the cytoplasm but favors its interaction with Fibrillarin1 in the nucleolus. TLCYnV carrying the AIM mutation displays enhanced pathogenicity in solanaceous plants. • Taken together, these data suggest that a new type of nuclear autophagy-mediated degradation of viral proteins through an exportin1-dependent nuclear export pathway restricts virus infection in plants.